Russian Consensus on Exo- and Endocrine Pancreatic Insufficiency After Surgical Treatment - Khatkov, Igor E.; Maev, Igor V.; Abdulkhalov, Sayyar R.; Alekseenko, Sergey A.; Allikhanov, Ruslan B.; Bakulin, Igor G.; Bakulina, Natalia V.; Baranovskiy, Andrey U.; Beloborodova, Ekaterina V.; Belousova, Elena A.; et al. (Turkish Journal of Gastroenterology, 2021)
The Russian consensus on exo- and endocrine pancreatic insufficiency after surgical treatment was prepared on the initiative of the Russian Pancreatic Club using the Delphi method. Its goal was to consolidate the opinions of national experts on the most relevant issues of diagnosis and treatment of exo- and endocrine insufficiency after surgical interventions on the pancreas. An interdisciplinary approach is ensured by the participation of leading gastroenterologists and surgeons.